Testing the Lucas critique in Malaysia: a comment - Ghazali, Noor Azlan; Ibrahim, Izani (Universiti Utara Malaysia, 2003)
The advent of ’rational expectation hypothesis’ (REH) in 1970’s sparked intense debate on the effectiveness of discretionary aggregate demand policies in influencing real economic activities. In line with this, the Lucas Critique (Lucas, 1976), that embodies the REH, questions the efectiveness of policy rule that frequently adopted in the set up of monetary policy. This commentary revisited the foundations of Lucas Critique and empirical studies reported by Habibullah, Azali dan Baharumshah (2001) (in short, HAB) on the validity of the critique within the Malaysian economy. The Lucas Critique is explained in greater detail based on an economic model that incorporates the behaviours of economic agents that form their expectation rationally. Brief empirical analysis indicates that rejection of Lucas Critique as proposed by HAB requires further invesigatations before it can be a generalization.